Synthesis and anti-tumor evaluation of new trisulfide derivatives - Haoyun An; Zhu, J.; Wang, X.; Xu, X.
New bis-aromatic and heterocyclic trisulfide derivatives 5, 7-10 were synthesized by optimizing lead dibenzyl trisulfide natural product (4)to evaluate their anti-tumor activities. Five compounds 5-7, 9, and 10 exhibited potent anti-tumor activities against eight different tumor cell lines with low cytotoxicity against HepG2. Initial SAR was discussed, and MOA of these anti-microtubule agents was suggested based on cell kinetic response patterns observed on RT-CES system.